2018
DOI: 10.2169/internalmedicine.9023-17
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of a Colonic Self-expandable Metallic Stent in Malignant Colonic Obstruction

Abstract: Self-expandable metallic stents (SEMSs) are used for the management of malignant colorectal obstruction. A patient who underwent colonic uncovered SEMS insertion for extraluminal stenosis in the splenic flexure of the transverse colon due to advanced gastric cancer is herein reported. The patient presented with a fracture of the colonic SEMS 494 days after SEMS insertion. Although various complications of stenting have previously been reported, the details of fractures of colonic SEMSs have not yet been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Increasing the quality of life, soothing pain and reducing symptoms of advanced disease is crucial from both medical and ethical perspective [1,2]. Selection of appropriate treatment should be based on careful and individual assessment of both advantages and disadvantages of available methods, together with possible complications [3][4][5]. Intestinal obstruction is one of the most common symptoms affecting even every second patient with advanced gynecologic tumors located in the pelvis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the quality of life, soothing pain and reducing symptoms of advanced disease is crucial from both medical and ethical perspective [1,2]. Selection of appropriate treatment should be based on careful and individual assessment of both advantages and disadvantages of available methods, together with possible complications [3][4][5]. Intestinal obstruction is one of the most common symptoms affecting even every second patient with advanced gynecologic tumors located in the pelvis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kadokura et al (10) suggested that it may be useful to select a stent with a stronger axial force or to select a shorter stent to reduce the risk of fracture in cases of short stenosis in bending sites, such as at the gastric outlet (prepyloric region to the duodenum). Takao et al (11) also presumed that prolonged friction between the stenotic and non-stenotic sections might have triggered stent fracture, and the inappropriate length and low axial force of the stent at the flexure led to stent fracture in a fracture case with colonic SEMS. Jin et al (12) showed that the incidence of stent fracture was 1.8% and 0.9% in the clinical outcomes of primary stenting and re-stenting for mGOO, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Миг-рация (дислокация) стента, частота которой состав-ляет 7-15 % случаев, происходит в основном при ис-пользовании покрытых эндопротезов. Она может быть связана с неадекватным позиционированием стента (ранняя миграция) или развиться после хи-мио-и лучевой терапии (поздняя миграция) [16,[37][38][39][40][41]. Болевой синдром является одним из посто-янных признаков эндопротезирования, обусловлен процессом расправления стента и, как правило, про-ходит спонтанно.…”
unclassified